Note on Price Discrimination and the A & P Case 1 - Adelman, M. A. (Quarterly Journal of Economics, 1951)
Journal Article Note on Price Discrimination and the A & P Case Get access Rashi Fein Rashi Fein Johns Hopkins University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 65, Issue 2, May 1951, Pages 271–280, https://doi.org/10.2307/1879538 Published: 01 May 1951